Trophic interactions among soil arthropods in contrasting land-use systems in Kenya, studied with stable isotopes - Lagerlöfa, Jan; Maribie, Crispus; Muturi, Jamleck (Elsevier, 2017)
Understanding how land use intensification changes organism communities and trophic interactions in soil is important for development of sustainable agriculture and forestry. We analysed the food web of soil arthropods with help of natural 13C/12C and 15N/14N ratios (δ13C and δ15N) in two habitats in the Kenyan Highland – a natural forest and an agricultural site on former forest land. Aims of the study: (1) to describe the structure and feeding relationships in the two systems for major soil arthropod groups, (2) to find differences in feeding strategies within major arthropod groups, (3) to determine if soil arthropod groups have the same trophic positions in forest and agricultural soil, (4) to evaluate if δ13C and δ15N can be explained by additional reasons, e.g. the physiology and C:N ratios of organisms. This is one of few studies of the trophic structure of soil arthropod communities in tropical ecosystems. It confirms that the structure is similar to comparable systems in the temperate zones. There was a large variation in δ15N among families of Oribatida, Mesostigmata and Collembola (the most common groups) indicating great variety in feeding ecology. Collembola and Diplopoda had comparatively high δ15N, indicating a contribution of animals to the diet. Although lower abundance and diversity of arthropods in the agricultural soil, the trophic positions of particular taxa, indicated as δ15N level, were similar to the forest. The δ13C values were negatively correlated to the C:N ratio, therefore increasing values of δ13C with trophic level could not be demonstrated.
Keywords: Collembola; Oribatida; Mesostigmata; 13-Carbon; 15-Nitrogen; Tropical soil